Cyclic stress-strain model for FRP-confined concrete considering post-peak softening. (1st October 2018) - Li, Pengda; Wu, Yu-Fei; Zhou, Yingwu; Xing, Feng
Abstract: The majority of existing cyclic stress–strain models for fiber reinforced polymer (FRP) confined concrete are applicable only to cases where post-peak strain hardening occurs. Cyclic model catering for strain softening is rare due to the lack of sufficient experimental data. Recent experimental tests on FRP-confined concrete cylinders involving strain-softening have identified new factors that have a significant effect on the cyclic behavior. Through an analytical study, a newly defined parameter, the effective confinement rigidity, is found to be a key factor governing the cyclic softening and hardening. By including the additional key factors and using the latest database with more strain-softening cyclic stress–strain curves, a stress–strain model of FRP-confined concrete subjected to cyclic loading considering both post-peak hardening and softening is proposed. Compared with the existing models, the proposed model can predict the cyclic behavior of FRP-confined concrete with better accuracy.